Kualitas Produk Brand Ambassador Content Marketing Terhadap Keputusan Pembelian Sunscreen Gloowandbe di TikTok Shop - Widitha Fasha; Ezra Karamang (TIN: Terapan Informatika Nusantara, 2026)
This study aims to analyze the influence of product quality, brand ambassadors, and content marketing on the decision to purchase Gloowandbe sunscreen products on TikTok Shop. The research method used is quantitative descriptive with quota sampling technique. Data collection was conducted through an online survey (questionnaire) to 100 respondents who were users or former users of Gloowandbe sunscreen aged 12-34 years on the TikTok Shop platform. The analyses used were validity-reliability tests, multiple linear regression, t-tests, f-tests, and R2 determination tests, with the help of SPSS 27 statistical tools. The results showed that simultaneously, product quality, brand ambassador, and content marketing had a positive and significant effect on purchasing decisions with an F value of 60,277 (Sig. 0.001 < 0.05). Partially, product quality is the most dominant variable influencing purchasing decisions with a value of t=5,351, followed by content marketing (t=3,572), and brand ambassador (t=2,702). The R2 value (coefficient of determination) shows that these three variables contribute 64,2% to purchasing decisions, while the remaining 35,8% is influenced by factors outside this study. Thus, it can be concluded that marketing strategies on TikTok Shop need to integrate consistent product quality with creative content and the selection of the right brand ambassadors to increase sales.